ANALYSIS OF TIRE FILLING RESULTS ON TIRE PATCH WITH AUTOMATIC TEMPERATURE CONTROLLER - I Made Arsana (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
An automatic temperature control tire patch are designed to make it easier to patch the tires, shorten the time and improve the quality of the tires. Tire fatch with automatic temperature controller are equipped with thermocouple and thermocontrol displays. Thermocouple is used as a temperature sensor and thermocontrol display as a medium that can be used to adjust and determine the tire temperature. This experimental study aims to determine the performance of tire patch tool in producing good quality patches with a relatively short time. Equipment and instruments used in this research are display thermocontrol, thermocouple, voltmeter, and amperemeter. The data obtained are then analyzed descriptively. The best patch results in this study were found at 70oC in the